38. The Uranium Mining Industry and Geology of the Monument Valley and White Canyon Districts, Arizona and Utah - Roger C. Malan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
The Monument Valley and White Canyon districts are in northeastern Arizona and southeastern Utah. Exploration and mining for uranium has been conducted in these districts since the late 1940's. In July 1965, ore reserves plus ore production at 174 properties were approximately 3.3 million tons of ore containing about 19 million pounds U3O8, of which about 10 per cent remained in reserves. The two largest mines, Monument No. 2 and Happy Jack, together account for about 45 per cent of the sum of production and reserves. Approximately half the deposits in these districts contain less than 1000 tons of ore. Nearly 5000 feet of Permian, Triassic, and Jurassic sedimentary rocks, mainly continental in origin, are exposed in these districts. All the important uranium deposits are in the Shinarump, the basal member of the Chinle Formation of Triassic age. The Shinarump lies on a widespread unconformity. It is composed of fluvial sediments, generally less than 100 feet thick, that were deposited by streams flowing from a source to the south. Most of the deposits are in an arcuate belt, convex to the west. This belt, 3 to 12 miles wide, extends from Monument Valley northward nearly 130 miles. It is along the western flank of the ancient Monument Valley-Monticello upland, an area that was slightly uplifted at the beginning and again at the end of deposition of the Shinarump. Erosion and subsequent reworking of the Shinarump sediments in the vicinity of this upland are postulated to have made possible the transportation, in solution, of the uranium contained in these sediments. The soluble uranium probably was carried by migrating ground water into sites favorable for precipitation in Shinarump beds bordering the upland. Thus, the original very small amounts of dispersed uranium in the early Shinarump sediments were accreted in the favorable belt where the accumulations of carbonaceous plant remains and their decay products provided a persistent reducing environment.